13y+(4y)(3x)+x=

Simple and best practice solution for 13y+(4y)(3x)+x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13y+(4y)(3x)+x= equation:


Simplifying
13y + (4y)(3x) + x = 0

Remove parenthesis around (4y)
13y + 4y(3x) + x = 0

Remove parenthesis around (3x)
13y + 4y * 3x + x = 0

Reorder the terms for easier multiplication:
13y + 4 * 3y * x + x = 0

Multiply 4 * 3
13y + 12y * x + x = 0

Multiply y * x
13y + 12xy + x = 0

Reorder the terms:
x + 12xy + 13y = 0

Solving
x + 12xy + 13y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13y' to each side of the equation.
x + 12xy + 13y + -13y = 0 + -13y

Combine like terms: 13y + -13y = 0
x + 12xy + 0 = 0 + -13y
x + 12xy = 0 + -13y
Remove the zero:
x + 12xy = -13y

Combine like terms: -13y + 13y = 0
x + 12xy + 13y = 0

The solution to this equation could not be determined.

See similar equations:

| 5x+15=15-3x+9 | | 4y-6=-22 | | 2(x-4)+3=4x+7 | | 6x^2+47x+92=0 | | (2x+28)=(3x+137) | | -24-7n=-8(3-6n) | | 42=3(2-3n)-6 | | -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 | | 0.625=-0.50x | | 88+1.5h=94+2h | | 85=3(x-1)+8x | | -5(k-1)-(-6k+1)=9 | | 7a^2+49a+60=0 | | (sin(x))*2=116 |

Equations solver categories